Microservices-Based Open-Source Video Conference Deployment for Optimized Online Learning Infrastructure - Davy Putra Ananda; Muhammad Fadhil Ramadhan Wicassono; Farhah Safrila Diva; Abdullah Rasyid; Juwita Istiqomah Trahira; Neny Rosmawarni (PT FORMOSA CENDEKIA GLOBAL, 2026)
The rapid advancement of information technology has fundamentally shifted the interaction paradigm in education from conventional methods to hybrid learning models. In this context, the availability of stable, real-time communication platforms has become crucial for maintaining the effectiveness of knowledge transfer. This study evaluates the implementation of Apache OpenMeetings v9.0.0 using Docker and WSL2 to provide efficient video conferencing. Using an experimental methodology, system performance was monitored during active sessions. Results show high resource efficiency with a stable CPU utilization of 4.94% and memory usage of 1.339 GiB. The system achieved a rapid startup velocity of 11.1 seconds, proving that containerization offers optimal isolation with minimal overhead. The study concludes that this architecture provides a lightweight, portable, and cost-effective solution for independent communication infrastructure in educational institutions.